Soft errors in modern electronic systems - Nicolaidis, Michael; SpringerLink (Online service). (Boston, MA Springer, 2011)
Soft Errors in Modern Electronic Systems describes the state-of-the-art developments and open issues in the field of soft errors. This work not only highlights a comprehensive presentation of soft errors related issues and challenges but also presents the most efficient solutions, methodologies and tools. The eleven chapters written by highly qualified experts provide a comprehensive description of the complex chain of the physical processes leading to the occurrence of soft errors, as well as of the numerous techniques and tools enabling the SER qualification of electronic systems during the design phase and after production, including: nuclear reactions of cosmic rays with the atmosphere (neutron and proton generation at ground level); nuclear reactions of atmospheric neutrons and protons with die atoms (secondary particles generation); coulomb interaction (ionization); device physics (charge collection); electrical simulation; event driven simulation; logic domain simulation; RTL simulation; hardware emulation, and radiation testing. The book also provides a comprehensive description of various hardware and software techniques enabling soft-error mitigation at moderate cost. Soft Errors in Modern Electronic Systems is a useful book for circuit and system designers, researchers, students and professors.
Soft Errors from Space to Ground: Historical Overview, Empirical Evidence, and Future Trends -- Radiation Induced Single-Event Effects: Physical Mechanisms and Classification -- JEDEC Standard on Measurement and Reporting of Alpha Particles and Terrestrial Cosmic Ray-Induced Soft Errors -- Cell-Level Modelling and Simulation -- Circuit and System Level Modelling and Simulation -- Hardware Fault Injection -- Accelerated Radiation Testing for Space Applications -- Testing for Ground-Level Applications -- Soft Error Mitigation Techniques -- Convergence of Mitigation Techniques for Soft Errors and Other Reliability Issues and Power Aware Mitigation Techniques -- Software Level Soft-Error Mitigation Techniques -- System Level Soft-Error Mitigation Techniques.
Electronic reproduction.
Keywords: Electronic systems; Soft errors (Computer science).; Electronic books